An Exploratory Research on the Issues in the Training of Teachers of French as a Foreign Language in the Public Science High Schools in the NCR and Region 7 - CAO, MARGARET FAITH (Philippine Humanities Review; Vol 20 No 2 (2018), 2021)
This paper aims to identify the issues in the Special Program in Foreign Languages (SPFL) of the K-12 curriculum particularly with regard to the French language program and its capacitation programs for teachers. In this exploratory study, the researcher addresses the lack of a standardized curriculum by looking into the context of teacher trainings for SPFL-French as well as the implementation of this special program in the National Capital Region and Region 7. Guided by Mangiante and Parpette’s framework of Needs Analysis for the development of language programs for special purposes (2004), the researcher conducted a series of purposive interviews with 18 key informants from the different sectors involved in the program such as the teachers, the students, the trainers and the Department of Education focal person for French. The researcher was able to pinpoint two major causes for the lack of a unified curriculum for teacher trainings: 1) the lack of a framework in the pedagogy of French as a foreign language, and 2) the general orientation of teacher training programs toward language proficiency development. As part of the objectives, the researcher ultimately proposes a conceptual framework for the creation of a standardized training program based on the findings that addresses not only the aspect of language proficiency development, but also the aspect of French as a foreign language pedagogy